Jack [compact disc, unabridged] - Robinson, Marilynne (Macmillan Audio, 2020)
John Ames Boughton is the beloved, erratic, and grieved-over prodigal son of a Presbyterian minister in Gilead, Iowa. In segregated St. Louis sometime after World War II, Jack falls in love with Della Miles, an African American high school teacher who is also the daughter of a preacher. Their fraught, beautiful romance is one of Robinson's greatest achievements.